Health disparities experienced by Black and Hispanic Americans with multiple myeloma in the United States: a population-based study. Issue 13 (10th November 2021) - Al Hadidi, Samer; Dongarwar, Deepa; Salihu, Hamisu M.; Kamble, Rammurti T.; Lulla, Premal; Hill, LaQuisa C.; Carrum, George; Ramos, Carlos A.; Heslop, Helen E.; Usmani, Saad Z.
Abstract: Hispanics and non-Hispanic (NH)-Blacks continue to face numerous health disparities related to multiple myeloma (MM). We aimed to analyze trends of MM-related hospitalizations and incidence of in-hospital mortality with a 10-year cross-sectional analysis of inpatient hospitalizations. The prevalence of MM-related hospitalizations was higher in NH-Blacks compared to NH-Whites (476.0 vs. 305.6 per 100, 000 hospitalizations, p < .001). MM-related in-hospital mortality was higher in Hispanics compared to NH-Whites and NH-Blacks (6.2 vs. 5.3%, p < .001). Using average annual percent change (AAPC), we found a statistically significant decline of in-hospital mortality among all MM patients except NH-Blacks (AAPC: −2.2, 95% confidence interval (CI) −4.7, 0.4, p = .47), who had the highest inpatient mortality in recent years. Multivariate analysis showed that NH-Blacks received fewer transplants, more blood product transfusions, fewer palliative care consults, less inpatient chemotherapy, and utilized more intensive care. Disparities in MM care for NH-Blacks and Hispanics continue to persist despite recent advancements in MM therapy.